"Far Beyond the Western Sea of the Arabs...": Reinterpreting Claims about Pre-Columbian Muslims in the Americas. (September 2014) - Francaviglia, Richard V.
<x content-type="archive" xml:space="preserve">Abstract</x> This article employs a historiographical approach to examine the controversial premise that Muslim explorers reached the Americas well before Columbus. Interestingly, those who originally conceived this premise in the early-to-mid twentieth century were not Muslims, and they emphasized the cultural or geographical (African and/or Arabian) rather than religious origins of alleged explorers to the New World. By the mid-to-late twentieth century, other proponents of the premise had created a popular literature that presented additional "evidence, " including language similarities, narratives, maps of exploration, and material culture artifacts. This evidence, which is described and evaluated herein, involves a number of fields or disciplines such as archaeology, history, and linguistics. Given the fragmentary and sometimes contradictory nature of this evidence, most professionals in varied fields are unconvinced that Islam predates Spanish exploration in the New World. That, however, has not deterred proponents, which now includes a growing number of Muslims who actively use religious magazines and websites to promote it. One can debate the premise, but perhaps a more productive way of addressing it may not be to determine whether it is "true" or "false, " but rather to examine it as socio-political narrative that serves several purposes. First, the premise is clearly revisionist in that it directly challenges the timeline of the European Age of Exploration. Second, it builds upon the commonly-held belief that a "Golden Age of Islam" (ca. 750 to 1275 ce) represented a superior culture that had accomplished great things before it was overwhelmed by western colonialism. By asserting the presence of Islam in the Americas before the arrival of Christians (and Jews), its supporters transform Islam into an indigenous American faith, thereby re-defining the ummah (worldwide community of Muslims) as predecessors, rather than recent arrivals, in the non-Muslim world.